DDT - a novel domain in different transcription and chromosome remodeling factors. - Doerks, T.; Copley, R.; Bork, P. (Trends in Biochemical Sciences, 2001)
Homology-based sequence analyses have revealed the presence of a novel domain (DDT) in bromodomain PHD finger transcription factors (BPTFs), chromatin remodeling factors of the BAZ-family and other putative nuclear proteins. This domain is characterized by a number of conserved aromatic and charged residues and is predicted to consist of three alpha helices. Recent studies indicate a likely DNA-binding function for the DDT domain.